ANALISIS SEMIOTIKA “PINANG DABUNG” DALAM TRADISI MASYARAKAT DESA SUNGAI PINANG KABUPATEN OGAN ILIR - M.Rizky Hadipratama Al-mubarok; Reza Aprianti; M Mifta Farid (Jurnal Prodi Ilmu Komunikasi, 2022)
Culture and tradition are two things that cannot be separated, In a tradition or custom there is usually a process that we ourselves do not know what the purpose and meaning of the process is if we look at it clearly, but if we look deeper there are many meanings that are hidden behind the symbols. the resulting symbol. The symbol or symbol is something that is used to designate something else, based on the agreement of a group of people, customs or traditions are generally found in the life cycle of a human being, starting from the birth process, to adulthood, marriage, then when the person dies, as for the process What is very important in a person's life cycle is getting married, why marriage is so important for someone, because by getting married, the lineage will continue so that later generations can continue the traditions and culture that existed before. This study discusses the meaning behind the areca nut and other handovers in the marriage process in the tradition of the Sungai Pinang village community. The research was conducted in Sungai Pinang Village, Ogan Ilir Regency. The theory used in this research is the theory of Semiotics model of Charles Sanders Pierce. The type of research used is descriptive with a qualitative approach. Data collection techniques using instruments in the form of Observation, Interview and Documentation of informants The results of this study indicate that the handovers given by the groom to the bride is evidence of seriousness and is ready to bear life both physically and mentally. Keywords: Tradition, Culture, Society, Symbol.